The Relationship of Smartphone Addiction and Depression, Anxiety and Stress among UTHM Diploma Students - Rahimi, Muhammad Ammar; Azrul Fazli, Aleeya Saffiyah; Tamrin, Hafizul Taufik; Nawi, Adnin Afifi (Multidisciplinary Applied Research and Innovation, 2026)
This research investigates the relationship between smartphone addiction and depression, anxiety and stress among University Tun Hussein Onn (UTHM) diploma students. Using the software Statistical Package for the Social Sciences (SPSS), 199 students completed a survey that included the Smartphone Addiction Scale (SAS) and the Depression Anxiety Stress Scale (DASS-21). With the highest mean score of (3.47), showing a reasonable degree of smartphone addiction, implying that smartphones are reused after putting it down. The mean scores for stress, anxiety, and depression length from 1.87 to 2.43, indicating a mild level of condition. Correlation analysis showed a moderate and statistically significant positive correlation relationship between smartphone addiction and both depression (r = 0.350, p < 0.001) and stress (r = 0.320, p < 0.001), while a weak but significant positive correlation was constructed with anxiety (r = 0.199, p = 0.007). The results suggested that this psychological illness is connected to an intensity of smartphone addiction. The main point is to focus on digital wellness action and mental health education for diploma students to limit the destructive effects of excessive smartphone use.